2014
DOI: 10.1002/2014jd021651
|View full text |Cite
|
Sign up to set email alerts
|

Lightning activity within tropical cyclones in the South West Indian Ocean

Abstract: Lightning activity within 70 tropical cyclones in the South West Indian Ocean is studied using a large data set (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013) provided by the World Wide Lightning Location Network (WWLLN). The radial and azimuthal distributions of lightning flashes are analyzed in three different regions of the basin: the open ocean, the Mozambique Channel, and the oceanic region up to 400 km off the eastern coast of Madagascar (ECM). Over the open ocean, lightning activity detected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 59 publications
(108 reference statements)
1
19
0
Order By: Relevance
“…The findings of Price et al (2009) are similarly seen in studies from Abarca et al (2011), Bovalo et al (2014, and Zhang et al (2015). Abarca et al (2011) used WWLLN data to look at 24 TCs in the Atlantic Basin, and found that intensifying TCs had up to twice as many lightning flashes in the inner core as TCs that did not intensify.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…The findings of Price et al (2009) are similarly seen in studies from Abarca et al (2011), Bovalo et al (2014, and Zhang et al (2015). Abarca et al (2011) used WWLLN data to look at 24 TCs in the Atlantic Basin, and found that intensifying TCs had up to twice as many lightning flashes in the inner core as TCs that did not intensify.…”
Section: Introductionsupporting
confidence: 75%
“…Abarca et al (2011) used WWLLN data to look at 24 TCs in the Atlantic Basin, and found that intensifying TCs had up to twice as many lightning flashes in the inner core as TCs that did not intensify. Using WWLLN data in the Southwest Indian Ocean, Bovalo et al (2014) studied 70 TCs between 2005 and 2013. Periods of increased lightning activity were found to be correlated with periods of rapid intensity change in those TCs.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of thunderstorms that occur over land find that the sum of CG and intracloud (IC) strikes (total lightning) are well correlated with updraft speed and thunderstorm convection structure [ Wiens et al , ]. Total lightning has also been used to probe the convective evolution and intensity of tropical storms [ De Maria et al , ; Bovalo et al , ]. Fierro et al [] used data from LASA (Los Alamos Sferic Array) [ Shao et al , ] to study the rapid intensification of Hurricanes Rita, Katrina, and Charley.…”
Section: Electrification In Tropical Stormsmentioning
confidence: 99%
“…The World Wide Lightning Location Network (WWLLN; Bovalo et al, ) global map with lightning stroke positions updated in every 10 min is used for real time locating the center of strong electrical activity and for adjusting the pointing azimuth of the camera. Since the detection efficiency of WWLLN is low, we also use the local lightning detection network, the infrared weather maps, and the Doppler radar images for locating the electrical center of the potential sprite‐producing thunderstorm.…”
Section: Data Acquisition Systemsmentioning
confidence: 99%